Red Queen: Glass Sword - Book 2 - Aveyard, Victoria (New York, NY HarperTeen, an imprint of HarperCollinsPublishers, 2016)
As the struggle between the growing rebel army and the blood-segregated world escalates, Mare, who has the red blood of the common folk but also the silver ability to control lightning, must fight against the darkness that has grown in her soul.
Keywords: Teenage girls -- Juvenile fiction; Ability -- Juvenile fiction; Blood -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Teenage girls -- Fiction; Ability -- Fiction; Blood -- Fiction; Kings, queens, rulers, etc -- Fiction; Government, Resistance to -- Fiction; Fantasy; Fantasy fiction